Impact of electricity tariffs and energy management strategies on PV/Battery microgrid performances. (November 2022) - Ouédraogo, S.; Faggianelli, G.A.; Notton, G.; Duchaud, J.L.; Voyant, C.
Abstract: Microgrids are considered as the future of the electricity production and networks; they often use photovoltaic (PV) production and battery storage system for supplying electricity to various loads. These microgrids need to be managed and controlled in order to operate efficiently. Five energy management (EMS) strategies more or less complex in their implementation have been developed. The most advanced rule-based control strategy integrates a PV production forecasting and a battery degradation into the decision process, thus improving the microgrid operation. An analysis of the influence of the electricity price profile on energy exchanges planning in the microgrid is realized. Four price profiles are used: peak and off-peak electricity prices, constant pricing, dynamic electricity pricing that reflects variations in electricity demand and production and a virtual electricity tariff considering the specificities of non-interconnected area as Corsica. The electricity tariff has an impact on the repartition of the energy flows and on the financial gain which justify more or less the utilization of such a microgrid. The influence of the battery size and the limitation of the electricity exchange power with the main grid were observed and depend substantially on the implemented EMS strategy.